2016
DOI: 10.1186/s13062-016-0136-3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha proteobacterial ancestry of the [Fe-Fe]-hydrogenases in anaerobic eukaryotes

Abstract: Eukaryogenesis, a major transition in evolution of life, originated from the symbiogenic fusion of an archaea with a metabolically versatile bacterium. By general consensus, the latter organism belonged to α proteobacteria, subsequently evolving into the mitochondrial organelle of our cells. The consensus is based upon genetic and metabolic similarities between mitochondria and aerobic α proteobacteria but fails to explain the origin of several enzymes found in the mitochondria-derived organelles of anaerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…It is assumed to be involved in syntrophic oxidation of propionate (Li et al, 2014) and contains a full set of genes coding for at least one "Fe-only hydrogenase" (Pelletier et al, 2008). This "Fe-only hydrogenase, " encoded by the hymABC structural and the hydEFG accessory genes, is in fact probably a [FeFe]-hydrogenase (Degli Esposti et al, 2016), which is frequently found in anaerobic prokaryotes. "Fe-only hydrogenase" was detected so far only in Archaea (Lubitz et al, 2014) and is intimately linked to methanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed to be involved in syntrophic oxidation of propionate (Li et al, 2014) and contains a full set of genes coding for at least one "Fe-only hydrogenase" (Pelletier et al, 2008). This "Fe-only hydrogenase, " encoded by the hymABC structural and the hydEFG accessory genes, is in fact probably a [FeFe]-hydrogenase (Degli Esposti et al, 2016), which is frequently found in anaerobic prokaryotes. "Fe-only hydrogenase" was detected so far only in Archaea (Lubitz et al, 2014) and is intimately linked to methanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In return, the endosymbiont may have consumed O 2 (as proposed previously 33 ) and provided the host with an intracellular pool of biological building blocks (for example, amino acids and co-factors that the host may not have been able to synthesize that were released passively or through endosymbiont death). On the basis of the absence of host-derived (that is, archaea-related) anaerobic 2-oxoacid catabolism genes (for example, ferredoxin-dependent 2-oxoacid oxidoreductase and NiFe hydrogenases) in eukaryotes 41,42 , the host presumably lost these during evolution towards the LECA. Notably, this loss might have consequently helped to simultaneously resolve catabolic redundancy (that is, 2-oxoacid catabolism in both host and symbiont) and O 2 sensitivity (that is, O 2 inactivates these enzymes 43,44 ).…”
Section: New Insights Into Eukaryogenesismentioning
confidence: 99%
“…None of the enzymes exclusive to anaerobic metabolism in eukaryotes has clear phylogenetic affinities to alphaproteobacterial homologs [94]. A recent report that claimed an alphaproteobacterial origin for eukaryotic [Fe]-hydrogenase [95] is invalidated by the failure to include relevant non-alphaproteobacterial homologs in the analysis (see [94] for a more comprehensive analysis). For several of these enzymes, including [Fe]-hydrogenase and ASCT, eukaryotic homologs group in phylogenetic trees into multiple distinct subfamilies, each of which is most closely related to enzymes from different bacterial taxa.…”
Section: Origins Of Proteins Involved In Anaerobic Metabolism and Mrosmentioning
confidence: 99%